GELİŞTİRİLMİŞ KALİTE KARŞILAŞTIRMA METODUYLA HİDROLİK KAZICI MAKİNE SEÇİMİ - Tibet Cebesoy (Pamukkale University Journal of Engineering Sciences, 1999)
Quality comparison equipment selection is essentially an equipment ranking method developed by Cokorilo and Milicic in 1991. The concept of this method is based on three matrixes models which are namely called as the machine technical characteristic matrix, parameter machine matrix and corresponding machine matrix respectively. However, the researchers mentioned have ignored to take into consideration the uncertainty in parameter machine characteristic matrix. Therefore, in this paper as a tool to manage this uncertainty and to improve the matrix explained , the use of fuzzy triangular technique is sought and thus as a numerical example, an application of the technique is given for a selection of hydraulic excavator. In quality based equipment selection, the results obtained from the application presented that the magnitude of fuzzy triangular technique is remarkable.